Internal quantum efficiency of III-nitride quantum dot superlattices grown by plasma-assisted molecular-beam epitaxy - Gacevic, Z.; Das, A.; Teubert, Jörg; Kotsar, Y.; Kandaswamy, P. K.; Kehagias, T.; Koukoula, T.; Komninou, P.; Monroy, E.; Justus Liebig University Giessen (My University, 2011)
We present a study of the optical properties of GaN/AlN and InGaN/GaN quantum dot (QD) superlattices grown via plasma-assisted molecular-beam epitaxy, as compared to their quantum well (QW) counterparts. The three-dimensional/two-dimensional nature of the structures has been verified using atomic force microscopy and transmission electron microscopy. The QD superlattices present higher internal quantum efficiency as compared to the respective QWs as a result of the three-dimensional carrier localization in the islands. In the QW samples, photoluminescence (PL) measurements point out a certain degree of carrier localization due to structural defects or thickness fluctuations, which is more pronounced in InGaN/GaN QWs due to alloy inhomogeneity. In the case of the QD stacks, carrier localization on potential fluctuations with a spatial extension smaller than the QD size is observed only for the InGaN QD-sample with the highest In content (peak emission around 2.76 eV). These results confirm the efficiency of the QD three-dimensional confinement in circumventing the potential fluctuations related to structural defects or alloy inhomogeneity. PL excitation measurements demonstrate efficient carrier transfer from the wetting layer to the QDs in the GaN/AlN system, even for low QD densities (similar to 10(10) cm(-3)). In the case of InGaN/GaN QDs, transport losses in the GaN barriers cannot be discarded, but an upper limit to these losses of 15% is deduced from PL measurements as a function of the excitation wavelength.
Keywords: quantum dot (QD) supperlattices; quantum wells (QW); GaN/AlN; InGaN/GaN; optical properties; ddc:530